Survey of Existing Pork Processing and Marketing Systems in Assam - R., Thomas; M.K. , Tamuli; Das , Anubrata (Journal of Meat Science, 2011)
A scientific approach has been applied to document the existing pork processing and marketing systems, and the study was conducted in Kamrup District, Assam. Different quality characteristics (carcass measurements, physico-chemical and microbiological) of pork marketed in this area were evaluated. The hygienic status of meat personnel/butchers and meat shops (which handle pork) were also assessed. Further, the work involved a survey to understand the requirements of pork consumers in the district. A total of 43 pork shops and 62 pork carcasses were assessed in the five different blocks under study. In this study 51 meat handlers and 300 pork consumers were evaluated. No pakka retail pork shops exist in any of the places under survey, irrespective of rural or urban areas. The microbiological characteristics of the pork carcasses, hands of meat personnel and the common facilities available in the pork shops viz. wooden cutting board, cutting knives etc. evaluated during the survey indicated that the counts for all the organisms considered were well above the prescribed limits for clean/hygienic pork.
Keywords: Pork processing; consumer evaluation; hygienic pork; clean pork